(untitled) (JURNAL GEOCELEBES, 2022)
This research was conducted in Kasihan, Pacitan, East Java with the aim of knowing the alteration zone and ore mineralization from mineral sediment systems based on the conductivity and resistivity of subsurface rocks in the study area. A geophysical method is needed to map area area area of the prospect of mineral deposits as well as mathematical models in the area research. One of the geophysical methods used in studies of mineral sediment cases is Time Domain Induced Polarization (TDIP). Measurement of Time Domain Induced Polarization method done with configuration dipole-dipole which is arranged relatively straight northeast-southwest as much 2 tracks, with each track having the length of 260 m with an initial space of 20 m electrodes. Targets of the TDIP Method can describe subsurface conditions as far as 48 m. The position of mineralization in skarn deposits in the Time Domain Induced Polarization method at a depth of 25 m below the surface topography shown by high resistivity values >2000 Ωm and >500 msec chargeability in dacite and limestone